2013
DOI: 10.1371/journal.pone.0079757
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Inhibitor, DPQ, Attenuates LPS-Induced Acute Lung Injury through Inhibiting NF-κB-Mediated Inflammatory Response

Abstract: Acute lung injury (ALI) is characterized by overwhelming lung inflammation and anti-inflammation treatment is proposed to be a therapeutic strategy for ALI. Poly (ADP-ribose) polymerase-1 has been demonstrated to be involved in tissue inflammation and one of its inhibitors, 3, 4-Dihydro-5[4-(1-piperindinyl)butoxy]-1(2H)-isoquinoline (DPQ), exerts anti-inflammatory effect. However, it is still unclear whether the DPQ possesses the protective effect on ALI and what mechanisms are involved. In this study, we test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 61 publications
2
39
0
1
Order By: Relevance
“…Studies have shown that neutrophil migration into the lung is at least partially mediated by the chemokines MIP-2 and KC (Lomas-Neira et al 2004). Indeed, both MIP-2 and KC have been linked to acute lung injury caused by systemic LPS (Wang et al 2013; Su et al 2014) by mediating neutrophil recruitment via activation of CXCR2 (Reutershan et al 2006). The work presented here shows that LPS-induced MIP-2 and KC expression in the lung was enhanced by ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that neutrophil migration into the lung is at least partially mediated by the chemokines MIP-2 and KC (Lomas-Neira et al 2004). Indeed, both MIP-2 and KC have been linked to acute lung injury caused by systemic LPS (Wang et al 2013; Su et al 2014) by mediating neutrophil recruitment via activation of CXCR2 (Reutershan et al 2006). The work presented here shows that LPS-induced MIP-2 and KC expression in the lung was enhanced by ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…VILI leads to local increases of TNFa, IL6 and IL1b, again suggesting the involvement of cytokines in the upregulation of Dio2 (Barca-Mayo et al 2011) via NF-kB activation (Lentsch et al 1998, Leeper-Woodford & Detmer 1999. Indeed, inhibiting NF-kB activation protects mice from LPS induced acute lung injury (Wang et al 2013). Interestingly, TH metabolism is also tightly linked with the innate immune system.…”
Section: Type 2 Deiodinasementioning
confidence: 99%
“…(reviewed in Jagtap and Szabo, 2005) and is comparable to the effect of other, earlier-generation PARP inhibitors, as well as genetic PARP1 deficiency in various models of critical illness and systemic inflammation (Jagtap et al, 2002;Liaudet et al, 2002;Soriano et al, 2002Soriano et al, , 2006Shimoda et al, 2003;Farivar et al, 2004;Szabo, 2007;Wang et al, 2013;Liu et al, 2015;Walko et al, 2015;Zhang et al, 2015). Thus, olaparib -although originally developed and optimized for the purposes of cancer therapy -performs as expected as a PARP inhibitor in the context of inflammation, organ injury and critical illness.…”
Section: Figurementioning
confidence: 97%